Testing the combination of albendazole, ivermectin and levamisole in lambs parasitized with multiple-resistant gastrointestinal nematodes - Suarez, Gonzalo (2014)
The goal of the current trial were: a) to characterize the efficacy of albendazole (ABZ), ivermectin (IVM) and levamisole (LEV), administered either alone or co-administered to lambs infected with multiple-resistant nematodes. One hundred and sixty eight (168) Corriedale lambs, naturally infected (epg range 200-5200) with multiple resistant gastrointestinal nematodes, were involved in the current trial. The animals were randomly allocated into eight groups (n=21 each), and orally treated either with ABZ (5 mg/kg), IVM (0.2 mg/kg), LEV (8 mg/kg) or with a combined formulation of ABZ+LEV, ABZ+IVM, LEV+IVM, ABZ+IVM+LEV, used at the same dose for each active ingredient. Fecal samples were collected a 4 (LEV), 10 (ABZ) and 14 (IVM) days post-treatment for clinical efficacy assessment by the faecal egg count reduction test (FECRT). The efficacy was 68% (IC95 34:85) for ABZ, 45% (IC95 -0.3:70) for LEV, 0% for IVM. Considering that only the incident rate for ABZ (day 10) was significantly higher than the observed for the control group, maintaining constant other variables, a positive interaction among the combined treatments was not observed (73% (IC95 49:86) for ABZ+LEV, 63% (IC95 31:81) for ABZ+IVM and 71% (IC95 33:87) for ABZ+IVM+LEV. In conclusion, with the high resistance status observed, the combined treatments did not offer a clinically relevant increase in efficacy against resistant nematodes.